Mental health services and resources for children with developmental disabilities and their families: scan of local practices, gaps, and opportunities created - Hanson, Jessica; Heslon, Kayla; Ogourtsova, Tatiana (Frontiers in Rehabilitation Sciences, 2023)
Background Mental health concerns in children with disabilities are common and have a significant and negative impact. Clinicians have reported high demand for this population to receive early, targeted, and family-centred mental health interventions. Objective We sought to map out and describe existing pediatric mental health services/resources for children with disabilities and their families across clinical sites and local and online communities. Methods Using a mixed-method triangulation study design, we outreached to clinical managers at the participating clinical sites and conducted a rapid online search of local in-person, telehealth, and web-based information. The nature, access method, admission criteria, target, focus, and other pertinent information were recorded and analyzed using descriptive statistics and a narrative synthesis approach. Results Eighty-one (n = 81) services/resources (in-person, n = 48; telehealth, n = 10; web-based information, n = 33) were identified. Few (n = 6, 13%) in-person services had a method of care access through an online booking portal. Nearly half of in-person resources (n = 23, 47%) had admission criteria specific for children with disabilities (e.g., diagnosis, age limit), and many (n = 32, 67%) required a formal referral. A small number of in-person and telehealth services targeted the mental health concerns of the entire family (n = 23, 47%; n = 2, 20%). Very few (n = 13, 16%) services incorporated follow-up support. Important gaps emerged for certain populations (e.g., children with cerebral palsy). Practitioners’ inadequate training when intervening with co-existing mental health demands of children with disabilities was noted by clinical managers. Conclusion Findings could be used to create a user-friendly database to easily identify suitable services and to advocate for services/resources that are lacking.